ENVIRONMENTAL BEHAVIOUR OF COMMUNITIES AROUND PEATLAND AREA OF PULANG PISAU, CENTRAL KALIMANTAN - Fauzi, Ridwan; Harianja, Alfonsus H.; Hidayat, M. Yusup; Witama, R. Onig; Purwanto, Budi; Marbun, Firdaus (Association of Indonesian Forestry and Environment Researchers and Technicians, 2025)
Sustainable peatland management must consider the social, economic, and environmental conditions of surrounding communities. Balancing these three pillars is essential for preserving the peatland's functions, which support the lives of various organisms dependent on the ecosystem. This research focuses on the behaviours of communities around peatlands in the Block C Peatland Management Unit (PMU) in Pulang Pisau Regency, Central Kalimantan. It investigates the social and economic variables influencing environmental behaviour in peatland management and utilization. Employing two methods-Participatory Rural Appraisal (PRA) and survey – this research aims to collect comprehensive data. Data processing is conducted by using tabulation and statistical inference. The PRA includes tools like village historical timelines, transects, seasonal calendars, and livelihood preferences, while the survey uses semi-structured interviews to assess individuals’ characteristics, perceptions, and participation in peatland management. The study reveals that villages encounter several challenges, including insufficient agricultural support, susceptibility to flooding, restricted access to clean water, and poorly functioning irrigation systems. Climate change has disrupted the dry season, resulting in lower rubber sap production. The limited availability of land for rice farming and a decreasing interest in forestry products are also significant concerns. The communities must shift their agricultural practice to adapt to climate change. While most respondents acknowledge the ecological importance of peatlands, greater involvement in their management is still needed. This underscores the need to enhance community capacity for peatland restoration and conservation. In conclusion, the findings stress the importance of incorporating social factors into peatland preservation efforts to foster environmental sustainability.